Probing activated radioprotection of simple hydrophilic phosphonic acids in aqueous solution. (May 2020) - Horne, Gregory P.; Zarzana, Christopher A.; Daubaras, Dayna L.; Pilgrim, Corey D.; Rae, Cathy; Faulkner, Richard F.; Kiddle, James J.; Mezyk, Stephen P.
Abstract: Previous investigation into the radiation chemistry of the ligand octylphenyl- N, N -diisobutylcarbamoylmethyl phosphine oxide (CMPO) and its analogues demonstrated their ability to undergo activated radioprotection in an organic solvent – a feature most advantageous for spent nuclear fuel reprocessing scenarios. This phenomenon was dependent on these organophosphorus compounds forming a sacrificial complex involving extracted nitric acid and the presence of an adjacent phenylphosphine oxide motif in the molecule. However, the hydrophobic nature of these compounds prevented elucidation of which components were essential for activated radioprotection; for example, does the phenylphosphine oxide motif only require protonation, or simply the presence of complexed nitrate anion(s), or both? To begin to address these questions, we report on the effect of dissolved nitrate on the radiation chemistry of a series of simple hydrophilic phosphonic acids (methyl, ethyl, phenyl, and benzyl) in aqueous solution. An extensive suite of gamma irradiations supported by high performance liquid chromatography and nuclear magnetic resonance techniques was used to demonstrate that all four compounds were unable to undergo activated radioprotection. Although some nitrate protection was observed, this was attributed to changes in the available suite of radiolysis products, and not to the formation of nitrate-phosphonic acid sacrificial complexes. The absence of activated radioprotection and evidence for the formation of a [PhPANO3 − ] complex further supports the necessity of complex formation to activate the radioprotection mechanism. Highlights: Gamma radiolysis of methyl, ethyl, phenyl, and benzyl phosphonic acids. Rate coefficients measured for key water and nitrate transients by pulse radiolysis. HPLC and NMR techniques measured no evidence of activated radioprotection. Dose constants showed some radioprotection attributed to nitrate scavenging processes.